Whole Genome Sequencing of Four Representatives From the Admixed Population of the United Arab Emirates - Daw Elbait, Gihan; Henschel, Andreas; Tay, Guan K.; Al Safar, Habiba S. (Frontiers in Genetics, 2020)
Whole Genome Sequences (WGS) of four nationals of the United Arab Emirates at 27X coverage or more were completed and described. The selection of suitable subpopulation representatives is informed by a preceding comprehensive population structure analysis. Representatives were chosen based on their central location within the subpopulation on a Principal Component Analysis (PCA) and the degree to which they were admixed. Novel genomic variation among the different subgroups of the UAE population are reported here. Specifically, the WGS analysis identified 4,161,067 to 4,798,806 variants in the four individual samples, where approximately 80% are Single Nucleotide Polymorphisms (SNPs) and 20% are insertions or deletions (indels). An average of 2.75% are found to be novel variants according to dbSNP 151. This is the first report of Structural Variants (SV) from WGS data from UAE nationals. There are 15,677 to 20,339 called SVs, of which around 13.5% are novel. The four samples shared 1,399,178 variants, each with distinct variants as follows: 1,085,524 (UAE S011), 1,228,559 (UAE S012), 791,072 (UAE S013) and 906,818 (UAE S014). These results show a previously unappreciated population diversity. The synergy of WGS and genotype array data is demonstrated through variant annotation of the former using 2.3 million allele frequencies for the local population derived from the latter technology. As the array and WGS technologies are complementary, the novel approach used here provided a more accurate sense of rarity as compared to non-local allele frequency studies as provided by GnomAD and thus facilitates additional variant prioritization.